The patellofemoral pain and osteoarthritis subscale of the KOOS (KOOS-PF): development and validation using the COSMIN checklist. Issue 17 (3rd March 2017) - Crossley, Kay M; Macri, Erin M; Cowan, Sallie M; Collins, Natalie J; Roos, Ewa M
Abstract : Background: Patellofemoral pain and osteoarthritis are prevalent and associated with substantial pain and functional impairments. Patient-reported outcome measures (PROMs) are recommended for research and clinical use, but no PROMs are specific for patellofemoral osteoarthritis, and existing PROMs for patellofemoral pain have methodological limitations. This study aimed to develop a new subscale of the Knee injury and Osteoarthritis Outcome Score for patellofemoral pain and osteoarthritis (KOOS-PF), and evaluate its measurement properties. Methods: Items were generated using input from 50 patients with patellofemoral pain and/or osteoarthritis and 14 health and medical clinicians. Item reduction was performed using data from patellofemoral cohorts (n=138). We used the COnsesus-based Standards for the selection of health Measurements INstruments guidelines to evaluate reliability, validity, responsiveness and interpretability of the final version of KOOS-PF and other KOOS subscales. Results: From an initial 80 generated items, the final subscale included 11 items. KOOS-PF items loaded predominantly on one factor, pain during activities that load the patellofemoral joint. KOOS-PF had good internal consistency (Cronbach's α 0.86) and adequate test–retest reliability (intraclass correlation coefficient 0.86). Hypothesis testing supported convergent, divergent and known-groups validity. Responsiveness was confirmed, with KOOS-PF demonstrating a moderate correlation with Global Rating of Change scores (r 0.52) and large effect size (Cohen's d 0.89). Minimal detectable change was 2.3 (groups) and 16 (individuals), while minimal important change was 16.4. There were no floor or ceiling effects. Conclusions: The 11-item KOOS-PF, developed in consultation with patients and clinicians, demonstrated adequate measurement properties, and is recommended for clinical and research use in patients with patellofemoral pain and osteoarthritis.